Short communicationAn aortic dissection treated with left main coronary artery stent implantation - Guz, Goksel; Altun, Ibrahim; Karaayvaz, Bilal; Akin, Fatih; Kocaaga, Mehmet; Atesal, Sebahattin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Retrograde coronary aortic dissection is a rare but dangerous complication of coronary angioplasty. Mostly seen in right coronary artery procedures, especially in chronic total oclussion lesions, and rarely seen in left side procedures. This is a case report of an aortic dissection complicated by coronary angioplasty of the left circumflex artery. Immediate stenting of the left main coronary artery successfully sealed the entry point of dissection and stabilized the patient.